2023
DOI: 10.1038/s41467-023-42318-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans adapts to the host environment through TOR-mediated remodeling of phospholipid asymmetry

Laura C. Ristow,
Andrew J. Jezewski,
Benjamin J. Chadwick
et al.

Abstract: Cryptococcus spp. are environmental fungi that first must adapt to the host environment before they can cause life-threatening meningitis in immunocompromised patients. Host CO2 concentrations are 100-fold higher than the external environment and strains unable to grow at host CO2 concentrations are not pathogenic. Using a genetic screening and transcriptional profiling approach, we report that the TOR pathway is critical for C. neoformans adaptation to host CO2 partly through Ypk1-dependent remodeling of phos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…We previously discovered a positive association between the ability of C. neoformans to grow in 5% CO 2 and their virulence level in mouse models of cryptococcosis ( 21 ). To understand the transcriptome differences between CO 2 -tolerant and CO 2 -sensitive strains, we previously carried out RNA deep sequencing experiments using the reference clinical strain H99, and the environmental isolates A1-84-14 and A7-35-23 in 5% CO 2 or ambient air ( 21 , 23 , 24 ). H99 and A1-84-14 are both CO 2 tolerant, while A7-35-23 is highly sensitive to CO 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously discovered a positive association between the ability of C. neoformans to grow in 5% CO 2 and their virulence level in mouse models of cryptococcosis ( 21 ). To understand the transcriptome differences between CO 2 -tolerant and CO 2 -sensitive strains, we previously carried out RNA deep sequencing experiments using the reference clinical strain H99, and the environmental isolates A1-84-14 and A7-35-23 in 5% CO 2 or ambient air ( 21 , 23 , 24 ). H99 and A1-84-14 are both CO 2 tolerant, while A7-35-23 is highly sensitive to CO 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To decipher the unique transcriptome response in the CO 2 -sensitive strain A7-35-23, we identified 466 genes that were differentially expressed (fold change > 2 and P < 0.05) in A7-35-23 (5% CO 2 vs ambient air) but showed no significant change in the CO 2 -tolerant strains H99 and A1-84-14. We decided to focus on 34 of the 466 genes that encode potentially secretory proteins with a signal peptide, because we recently showed that CO 2 potentiates antifungal drugs that interfere with membrane ( 21 , 23 ) (Table S1). Of these 34 genes, 16 genes encode products with annotation of predicted function and 14 genes are covered in the H99 deletion sets generated by Dr. Hiten Madhani’s group.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this notion, Sch9 kinase and Sit4 phosphatase have been identified as necessary components for BBB infection ( Jin et al., 2020 ). Recently, the TOR pathway has been implicated in adaptation to the host environment through Ypk1-dependent phospholipid asymmetry remodeling ( Ristow et al., 2023 ). Besides kinases and phosphatases, Zfp1, which is homologous to Sfp1 and is involved in nutrient sensing and the cell cycle as a downstream transcription factor of TOR signaling in S. cerevisiae , is required for virulence in C. neoformans .…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that these proteins are promiscuous and transport a diverse array of substrates, and coupled with the expanded repertoire of PDR genes in Cryptococcus , it is not surprising to find roles other than traditional efflux pumps and subsequent resistance to xenobiotics. PDR6 has also been implicated in aging and replicative life span (13), and most recently, PDR9 , a full-length PDR gene in the same clade as AFR1 , was found to play a role in CO 2 tolerance via an unknown mechanism that may involve phospholipid flipping (48). Hence, PDR6 may act through multiple direct and indirect mechanisms to modulate the inflammatory host response, such as by secreting immunomodulatory molecules, aiding in maintaining the correct PM fluidity by regulating ergosterol transport, and preventing exposure of surface PAMPs by supporting correct cell wall and/or capsule architecture.…”
Section: Discussionmentioning
confidence: 99%